The obedience of the church as a prelude to the parousia : ecclesial and temporal factors in New Testament eschatology - Wethmar, Conrad Johannes (University of Pretoria, 2013)
Thesis (PhD (Dogmatics and Christian Ethics))--University of Pretoria, 2007.